2020
DOI: 10.3389/fvets.2020.568249
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in TLR4 Gene Associated With Somatic Cell Score in Water Buffaloes (Bubalus bubalis)

Abstract: Considering the importance of the diseases affecting the productive performance of animals in the dairy industry worldwide, it is necessary to implement tools that help to control and limit the occurrence of such diseases. As the increased somatic cell counts (SCC) are a direct expression of the inflammatory process, they are candidates to become the usual parameter for assessing udder health regarding milk quality and for monitoring mastitis incidences. Toll-Like Receptors are membrane proteins that play a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Significantly higher expression levels of TLR4 gene have been found in blood neutrophils of ketotic cows [42]. Moreover, Roldan-Montes et al [43] found in milk, a significant association between the identified…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Significantly higher expression levels of TLR4 gene have been found in blood neutrophils of ketotic cows [42]. Moreover, Roldan-Montes et al [43] found in milk, a significant association between the identified…”
Section: Discussionmentioning
confidence: 92%
“…Significantly higher expression levels of TLR4 gene have been found in blood neutrophils of ketotic cows [ 42 ]. Moreover, Roldan-Montes et al [ 43 ] found in milk, a significant association between the identified polymorphisms of the TLR4 gene and the somatic cell score of water buffaloes. A significant down-regulation in the expression of TLR4 gene in LPS-stimulated BV-2 microglial cell line of rats was observed in vitro [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, rs8193069 was found to be significantly associated with SCC in the trialled Holstein cow population, showing that individuals with genotype TT had higher SCC. As increased SCC in the milk indicates long term intra‐mammary inflammation (Roldan‐Montes et al., 2020 ), a lower SCC is free of, or at least, low infection (Pighetti & Elliott, 2011 ). Therefore, the allele C of rs8193069 is the major allele, in other words, individuals with genotype CC would have a greater genetic potential for mastitis resistance under the similar environment.…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 polymorphisms are not associated only with disease resistance/susceptibility but also with somatic cell count (SCC)/SCS (Chen et al, 2022;Mišeikienė et al, 2020;Noori et al, 2013;Roldan-Montes et al, 2020;Sharma et al, 2006a;Wang et al, 2007), milk production traits (Chen et al, 2022;Mišeikienė et al, 2020;Noori et al, 2013;Wang et al, 2018;Zhou et al, 2017), lactation persistency (Sharma et al, 2006a), infectious bovine keratoconjunctivitis (Kataria et al, 2011), and maternal calving difficulty (Mullen et al, 2018). Three studies by Sharma et al (2006aSharma et al ( , 2006bSharma et al ( , 2015, reported the same allele, allele G from the TLR4 c.-226G>C SNP, to be associated with lower SCS, longer lactation persistency and lower risk of MAP infection in Canadian Holstein.…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%
“…Actual CM incidence has the potential to be quite an accurate indicator, but data on CM incidence are costly and difficult to acquire (Muhasin Asaf et al, 2014; Russell et al, 2012). Further, in that case, subclinical mastitis, which is the most common form of mastitis (Roldan‐Montes et al, 2020), would be overlooked. Due to the relatively easy access to SCC data compared to mastitis incidence, SCC or SCS is usually used as the indicator trait for both clinical and subclinical mastitis (Muhasin Asaf et al, 2014; Noori et al, 2013; Roldan‐Montes et al, 2020; Stear et al, 2017).…”
Section: Research Limitationsmentioning
confidence: 99%